2017
DOI: 10.1002/14651858.cd001146.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Early (< 8 days) systemic postnatal corticosteroids for prevention of bronchopulmonary dysplasia in preterm infants

Abstract: Early (˜8 days) systemic postnatal corticosteroids for prevention of bronchopulmonary dysplasia in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
207
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(214 citation statements)
references
References 119 publications
5
207
0
2
Order By: Relevance
“…Breaking this cycle using systemic corticosteroids is possible, and there are now over 50 randomised controlled trials studying the risks and benefits of various corticosteroid regimens [133, 134]. Dexamethasone increases the chance of successful extubation and reduces BPD but at the expense of increased risk of neurodevelopmental sequelae if used in the first week [133, 135]. We previously recommended that the smallest effective dose should be used and only for babies at highest risk of BPD such as those who remain ventilator-dependent after 1–2 weeks.…”
Section: Strategiesmentioning
confidence: 99%
“…Breaking this cycle using systemic corticosteroids is possible, and there are now over 50 randomised controlled trials studying the risks and benefits of various corticosteroid regimens [133, 134]. Dexamethasone increases the chance of successful extubation and reduces BPD but at the expense of increased risk of neurodevelopmental sequelae if used in the first week [133, 135]. We previously recommended that the smallest effective dose should be used and only for babies at highest risk of BPD such as those who remain ventilator-dependent after 1–2 weeks.…”
Section: Strategiesmentioning
confidence: 99%
“…Studies have shown that the postnatal application of systemic corticosteroids for the prevention or treatment of BPD may facilitate extubation and decrease the incidence of BPD . However, systemic corticosteroids have been linked to NDI and CP, especially in infants receiving dexamethasone during the first week after birth . To minimize the adverse effects of systemic corticosteroid administration, IAC has become a common strategy for the prevention and treatment of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 However, systemic corticosteroids have been linked to NDI and CP, especially in infants receiving dexamethasone during the first week after birth. 8,11 To minimize the adverse effects of systemic corticosteroid administration, IAC has become a common strategy for the prevention and treatment of BPD. Previous studies have shown that IAC significantly reduces mucosal edema and mucus secretion, improves the gas exchange and oxygenation index, and alleviates respiratory hypersensitivity, airway resistance and the pulmonary inflammatory response.…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations